2016
DOI: 10.1063/1.4962421
|View full text |Cite
|
Sign up to set email alerts
|

A non-scale-invariant form for coarse-grained diffusion-reaction equations

Abstract: The process of mixing and reaction is a challenging problem to understand mathematically. Although there have been successes in describing the effective properties of mixing and reaction under a number of regimes, process descriptions for early times have been challenging for cases where the structure of the initial conditions is highly segregated. In this paper, we use the method of volume averaging to develop a rigorous theory for diffusive mixing with reactions from initial to asymptotic times under highly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 54 publications
0
1
0
Order By: Relevance
“…They also found that the dispersion coefficient was a function of the initial configuration. In a sequence of two papers, Wood (2009, equations (17) and (29)) and Wood & Valdés-Parada (2013) developed theories that explicitly included the influence of the initial condition as a source term in the averaged mass balance equation; this process was then used by Ostvar & Wood (2016) to describe the average diffusion and reaction from an initial (unmixed) configuration. Independently, Balakotaiah & Ratnakar (2010) also developed balance expressions specifically for the Taylor dispersion problem in which source terms arising from the initial conditions were employed; a Kramers-Moyal-like expansion was used, but truncated at second order.…”
Section: Introductionmentioning
confidence: 99%
“…They also found that the dispersion coefficient was a function of the initial configuration. In a sequence of two papers, Wood (2009, equations (17) and (29)) and Wood & Valdés-Parada (2013) developed theories that explicitly included the influence of the initial condition as a source term in the averaged mass balance equation; this process was then used by Ostvar & Wood (2016) to describe the average diffusion and reaction from an initial (unmixed) configuration. Independently, Balakotaiah & Ratnakar (2010) also developed balance expressions specifically for the Taylor dispersion problem in which source terms arising from the initial conditions were employed; a Kramers-Moyal-like expansion was used, but truncated at second order.…”
Section: Introductionmentioning
confidence: 99%